Forward Genetic Analysis of the CpG Hypo-response in Wild-derived MOLF/Ei Mice. - Moseman, Annie. (2017)
Abstract: Toll-like receptors (TLRs) are critical sensors in the recognition of microbial pathogens that activate the innate immune system and subsequently direct adaptive immune responses. CpG motif-containing oligodeoxynucleotides (CpG ODNs) mimic the immunostimulatory properties of bacterial DNA in innate and adaptive immune cells through toll-like receptor 9 (TLR9) signaling. Whether all cell types that express TLR9 exploit identical activation pathways is not known. Not all anatomical sites are equally susceptible to microbial exposure and cell- types that survey these sites for possible infection may well employ distinct mechanisms to sense the presence of pathogenic invaders. In a similar vein, the extent to which genetic differences might contribute to TLR9-driven responses remains to be explored as well. There are approximately 450 established laboratory inbred mouse strains. These strains can be classified into two groups based on their origin. Classical inbred strains were derived from fancy mice during the twentieth century while wild-derived laboratory strains were derived directly from wild-caught mice. There are three major subspecies, Mus musculus musculus, Mus musculus castaneus and Mus musculus domesticus, which diverged about a million years ago. Hybridization between M. m. musculus and M. m. castaneus resulted in the Mus musculus molossinus subspecies. Here we have used an evolutionarily divergent wild-derived mouse strain, MOLF/Ei (M. m. molossinus), to uncover novel genes and examine their roles in CpG ODN activation of peritoneal macrophages. While peritoneal macrophages from standard laboratory mouse strains are responsive to CpG DNA activation, peritoneal macrophages from the wild-derived inbred mouse strain, MOLF/Ei, are hypo-responsive. We have used a forward genetic approach to analyze the CpG response in peritoneal macrophages from N2 backcross mice. Our genome-wide linkage studies show a role for the mannose receptor, C type 1 (Mrc1) in CpG trafficking in wild-derived MOLF/Ei peritoneal macrophages. Additional mapping studies also show a critical role for cathepsin L (Ctsl) in TLR9-driven responses in primary mouse peritoneal macrophages. These findings reveal novel functions for MRC1 and CTSL and demonstrate that wild-derived mice are useful for understanding naturally occurring regulators of inflammatory responses in innate immune pathways.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Immunology.; Advisor: Alexander Poltorak.; Committee: Stephen Bunnell, Peter Brodeur, and Erik Selsing.; Keywords: Immunology, and Genetics.